2002
DOI: 10.1128/aac.46.1.242-244.2002
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Pharmacokinetics and Penetration of BMS 284756 into an Inflammatory Exudate

Abstract: The pharmacokinetics of a single dose of BMS 284756 were determined following oral administration of a 600-mg dose to eight healthy male volunteers. Concentrations of the drug were measured in plasma and a cantharidine-induced inflammatory exudate by a microbiological assay. The mean peak concentration in plasma of 10.4 g/ml (standard deviation [SD], 1.3 g/ml) was attained at a mean time of 1.2 h (SD, 0.5 h) after the dose. The penetration into the inflammatory exudate was 82% (SD, 15.7%). A mean peak concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…It is therefore likely that staphylococcal fluoroquinolone resistance will persist in the Asia-Pacific region. Whether an agent such as garenoxacin has less potential to select for resistant mutants and therefore maintain clinical utility is unclear, but its high potency compared to its pharmacokinetics (35) suggests that this may be the case.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that staphylococcal fluoroquinolone resistance will persist in the Asia-Pacific region. Whether an agent such as garenoxacin has less potential to select for resistant mutants and therefore maintain clinical utility is unclear, but its high potency compared to its pharmacokinetics (35) suggests that this may be the case.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study of moxifloxacin distribution in healthy human volunteers by investigation of cantharides-induced inflammatory exudate demonstrated that following a single oral or IV dose (400 mg), moxifloxacin penetrates rapidly into the site of an inflamed lesion. 15 The concentration of moxifloxacin in plasma versus inflammatory exudate reached a C"'"' of 4.9 vs 2.8 mg/I at approximately I vs 3.1 hours post oral dose. The half-life was 8.3 vs IO hours over the study time and achieved an AUC of 39.0 vs 32.5 mg/1/h.…”
Section: Discussionmentioning
confidence: 96%
“…To evaluate this parameter, several experimental models have been elaborated. Among skin blisters developed either by using mild suction (13–15) or by direct application to the skin, an irritating agent – cantharidin – in the form of a plaster (16, 17) or ointment (18, 19) containing 0.2–0.25% of this compound, have been used more frequently todate.…”
Section: Discussionmentioning
confidence: 99%